Postkomodifikasi Media Sosial Ridwan Kamil dan Ganjar Pranowo dalam Perspektif Wacana Foucaldian - Dudi Rustandi; Freddy Yusanto (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
Ahead of the 2024 election, some figures are familiar with mediating themselves with social media. The purpose of this study is to understand the persona and analyze the post-commodification of social media on Ridwan Kamil and Ganjar Pranowo's uploads through Michel Foucault's critical media discourse approach. The data collection technique uses textual observation techniques through the Instagram pages of the two figures. The results show that in the post-commodification perspective of social media, Ridwan Kamil and Ganjar Pranowo's uploads have content and relations with power. The discourses of these two figures have a strong relationship with the practice of management either as themselves or as public officials. The research impacts the theoretical output of practical activities carried out by political figures so that it can be a reference in learning critical communication in social media. Another effect, this analysis can contribute ideas and knowledge in the context of new media discourse that can be used as a reference in communication and media studies.